2017
DOI: 10.18203/2320-1770.ijrcog20172308
|View full text |Cite
|
Sign up to set email alerts
|

Effect of maternal ABO blood type on birth weight and preeclampsia

Abstract: Background: ABO blood group has been recognized as a risk factor for distinct disease states. The association between ABO blood group and adverse pregnancy outcomes has not been extensively studied, especially in relation to birth weight and preeclampsia (PE). The aim of the present study is to determine whether ABO blood group contributes to the adverse pregnancy outcomes including low birth weight and PE.Methods: Medical data including ABO phenotypes were collected from hospital electronic database and retro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 11 publications
1
20
0
1
Order By: Relevance
“…In many low-income countries, LBW is associated with lower socioeconomic status, female sex, increasing parity, young maternal age, low level of maternal education, low caloric intake, malaria, and general morbidity [8–10]. Furthermore, studies have demonstrated a link between ABO blood groups and birth weight [11, 12]. For instance, in Turkey, Beyazit et al reported that pregnant women with type B blood group had significantly lower birth weight babies compared with women with other ABO blood groups [11].…”
Section: Introductionmentioning
confidence: 99%
“…In many low-income countries, LBW is associated with lower socioeconomic status, female sex, increasing parity, young maternal age, low level of maternal education, low caloric intake, malaria, and general morbidity [8–10]. Furthermore, studies have demonstrated a link between ABO blood groups and birth weight [11, 12]. For instance, in Turkey, Beyazit et al reported that pregnant women with type B blood group had significantly lower birth weight babies compared with women with other ABO blood groups [11].…”
Section: Introductionmentioning
confidence: 99%
“…Compared to other blood groups, Placental protein 13 was reported to bind more strongly to AB blood group (15). Also, high levels of coagulation factors (including factor VIII and von Willebrand factor) leading to preeclampsia and triggering pathophysiological events were reported in women with AB blood group (11). The fact that thromboembolic events are more common in other blood groups compared to the O blood group is another evidence supporting the association between the AB blood group and preeclampsia (15,18).…”
Section: Discussionmentioning
confidence: 97%
“…The fact that thromboembolic events are more common in other blood groups compared to the O blood group is another evidence supporting the association between the AB blood group and preeclampsia (15,18). However, there are studies in the literature indicating that there is no relationship between preeclampsia and the ABO blood group (9)(10)(11)(12). In these studies, other factors (such as obesity, cardiovascular disease, and hypertensive diseases) were suggested to play a role in the development of preeclampsia except for the ABO blood group (9).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations